Estudo sobre a composição estética da obra Canaã, de Graça Aranha - Barbara Del Rio Araujo (2013)
The aim of this paper is to develop a study about the novel Canaã (1902), by Graça Aranha, searching to reach an interpretation line able to provide a reflection about the relation between the book and the social-historic materials. The interest is demonstrating the aesthetic dispositive arrange from the first book of maranhense writer´s represents a human and social reality historically situated. Thus, although it is used to be appointed, by the critic studies, as a disarticulated narrative, due to inconsistencies between the happenings that occurs and the concepts that it elaborates, the novel revels only an apparent lack of historicization. A mindful analyze can show that book´s formal failure, attributed several times as a composition mistake and writer´s lack of expertise, is one of the manners to represent the reality, which express its mimeses power. By the comprehension about how the book was situated in the Brazilian literature scenery and approached in the critic tradition, we´ll search to develop a study about the Canaã literary configuration.